Multicast security : issues and solutions - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran (IIUM Press, 2011)
The rapid growth of multicast communications has lead to wide use of the Internet for both individual and commercial distributed applications. Multicast communication is defined as an efficient way to distribute rich media to multiple users or participants simultaneously over the Internet. This is efficient in many applications including Internet video transmissions, news feeds, stock quotes, software updates, live multiparty conferencing, online video games and shared whiteboards. Thus, the need for secure transmission of multicast streams is considered as an important issue. However, potential security threats to multicast communications are similar to those encountered in unicast transmissions. These threats include the unauthorized creation, alteration ,destruction and illegitimate use of data. In case of multicast traffic, the inherent broad scope of a multicast session, the potential for attacks may be greater than that countered in unicast traffic. It is required to secure these services while maintaining the trade-off between efficiency and performance